From museum to memory institution: the politics of European culture online - Stainforth, Elizabeth (Museum and Society, 2017)
Museums, libraries and archives have long been considered the retainers of some form of collective memory. Within the last twenty years, the term ‘memory institution’ has been coined to describe these entities, which is symptomatic of the fact that such places are increasingly linked through digital media and online networks. The concept of the memory institution is also part of the vocabulary used to promote broader cultural integration across nations, and appears in discussions of European heritage and in policy documents concerning the digitization of cultural heritage collections. To explore the relationship between cultural heritage, memory and digital technology further, this paper will examine the large-scale digitization project Europeana, under which museums, libraries and archives are re-defined as cultural heritage institutions or memory institutions. My purpose is to trace the conceptual trajectory of memory within this context, and to address how the idea of a European cultural memory structured by technology holds implications for institutions traditionally associated with practices of remembering. Key words: Cultural heritage, collective memory, digitization, network, memory institution, Europe, integration